Development of High Performance Inter-Car Oil Damper with Pressured N2 Gas for Railway Vehicle - TANIFUJI, Katsuya; OGAWA, Takayuki; NAMBA, Kouichirou; SAKANOUE, Kei (Transactions of the Japan Society of Mechanical Engineers Series C, 2006)
This paper deals with a development of inter-car oil damper used in longitudinal direction between railway vehicles. Loading tests and field-tests as well as theoretical analysis are conducted to understand the characteristics of conventional damper working in practical displacement. Based on the test results, an oil damper with pressured N2 gas is developed and the damping performance is examined in the numerical simulation. The trial dampers are equipped on Series 700 Shinkansen vehicles for running tests. It is shown that pressured N2 gas in a longitudinal damper maintains high bulk module of oil, as a result, higher kinetic energy can be absorbed and riding comfort is improved especially in tunnel sections.